Flashforward Language Style Analysis in Bugis Song Lyrics by Selfie Yamma - Murti Sri Devi Aggraeni; Daru Winarti; Jumardin Muchtar (JELITA, 2024)
The objective of this research is to examine the "flashforward" language style of Bugis music lyrics performed by Selfie Yamma, with a focus on cultural, linguistic, and musical backgrounds. Information was gathered from the lyrics of the songs collected from relevant sources. The process of data analysis included organizing the data, simplifying the data, presenting the data, and summarizing the data. The analysis findings indicate that the "flashforward" language style plays a crucial role in forming a distinct and exclusive ambiance in Bugis song lyrics. Utilizing flashforward language style in song lyrics enhances the understanding and expression of the message, providing a new perspective for interpretation. Language in Bugis culture is not only a means of communication in song lyrics; it also represents the traditional values, beliefs, and historical experiences of the Bugis people. The use of "flashforward" language in song lyrics enhances emotional and cognitive engagement with the audience by adding a dynamic and imaginative element to the interpretation.